The determinant of reconsumption intention: a study of Indonesian traditional herbal medicine consumers - Elizabeth; Margono; Fatchur Rohman; Ananda Sabil Hussein (Cogent Business & Management, 2024)
Although there have been several studies on reconsumption intention, no specific studies investigate how perceived value can increase reconsumption intention in herbal medicine consumers. This study investigated the effect of perceived value on reconsumption intention among Indonesian herbal medicine consumers through trust and customer engagement. It involved 425 herbal medicine consumers in Indonesia with a purposive sampling technique. Data analysis employed covariance-based structural equation modeling (CB-SEM). The findings suggested that perceived value does not have a significant direct effect on reconsumption intention, yet it is mediated by customer engagement. Meanwhile, trust does not play a significant mediating role in the relationship between perceived value and reconsumtion intention. Therefore, it provides new insight into how consumer perceived value can enhance reconsumption intention through engagement and trust, which can serve as an input for herbal medicine practitioners to implement the appropriate marketing strategies.
Keywords: 650; Perceived value; trust; customer engagement; reconsumption intention; herbal medicine